ANALISIS PERILAKU KONSUMTIF PADA MAHASISWA - Annisa Amalia; Hana Suraya Khairunnisa; Nadiah Indrianti; Hisny Fajrussalam; Ossi Marga Ramadhan (IZZI: Jurnal Ekonomi Islam, 2023)
The purpose of this study is to find out and analyze how the consumptive behavior of students and Islamic views are related to recommended consumptive behavior. In this study using a qualitative approach method by distributing assessment questionnaires containing several questions according to consumptive indicators and conducting interviews to obtain data from research target students. The results of the data will be presented which will be concluded by the author. The results of this study, it was found that Indonesian University of Education Telecommunications System Students from class 2019-2022 are not consumptive and implement the recommendations of the Qur'an and scholars by being consumers who are not excessive or extravagant in shopping, but are consumers who are simple and prioritize dharuriyah needs or basic needs.